2020
DOI: 10.3390/met10111513
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Potential of Lithium–Sulfur Batteries—A First Concept Using Thermal and Hydrometallurgical Methods

Abstract: High-energy battery systems are gaining attention in the frame of global demands for electronic devices and vehicle electrification. This context leads to higher demands in terms of battery system properties, such as cycle stability and energy density. Here, Lithium–Sulfur (Li–S) batteries comprise an alternative to conventional Li-Ion battery (LIB) systems and can be asserted to next-generation electric storage systems. They offer a promising solution for contemporary needs, especially for applications requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[ 264–266 ] However, some approaches were reported in the literature. [ 267 ] While the challenges with regard to the Li metal are discussed in the section above, the separator, binder and electrolyte can be subject to similar recycling procedures which are used or investigated for LIBs. Nevertheless, it is necessary to carry out further studies on the applicability and possible upscaling for industrial processes.…”
Section: Recycling Of Future Batteries—current Approaches and Challen...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 264–266 ] However, some approaches were reported in the literature. [ 267 ] While the challenges with regard to the Li metal are discussed in the section above, the separator, binder and electrolyte can be subject to similar recycling procedures which are used or investigated for LIBs. Nevertheless, it is necessary to carry out further studies on the applicability and possible upscaling for industrial processes.…”
Section: Recycling Of Future Batteries—current Approaches and Challen...mentioning
confidence: 99%
“…In best cases, these gases can be converted to elemental sulfur or precipitated as sulfides, for example with copper. [ 267 ] However, in combination with the highly reactive Li metal anode, separation and handling of the electrodes will complicate future recycling.…”
Section: Recycling Of Future Batteries—current Approaches and Challen...mentioning
confidence: 99%
“…A first recycling approach can be found in [18]. Here, lithium was recovered by conventional leaching.…”
Section: Introductionmentioning
confidence: 99%
“…Li-losses in the different filter cakes were found and Li-losses in the residual filtrate and impurities in the product. An LCA (Life Cycle Analysis) of this process path for lithium-ion batteries demonstrated that pH-adjustment by NaOH, which was used in [18], significantly contributes to the GWP (global warming potential), TAP (terrestrial acidification potential) and FDP (fossil depletion potential) of this process [19]. NaOH production makes up the largest part in FDP and GWP, hence it demonstrates the highest impact regarding the environmental impact categories of the process [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation